Modern contraceptives use by client choice and associated factors in public health facilities of Nekemte town, Western Ethiopia - Gebeyehu Abera; Tariku Tesfaye Bekuma; Tadesse Tolossa (Elsevier, 2021)
Background: Lack of client choice in the contraceptive use results in unmet need for family planning and discontinuation of family planning (FP) methods as well. This study was aimed to assess the magnitude and factors associated with modern contraceptive use by client choice among contraceptive users at public health facilities in Nekemte town, Western Ethiopia. Methods: Facility based cross-sectional study was conducted among 282 systematically selected women of modern family planning users in public health facilities of Nekemte town. Epi-data version 3.1 and SPSS version 21 statistical software were used for data entry and analysis, respectively. A bivariable and multivariable logistic regression analyses were employed to identify the magnitude and factors associated with modern contraceptive use by client choice. Results: The magnitude of contraceptive use by client choice was 73.4 (95% CI: 68.8, 78.4). The results of multivariable logistic regression analyses showed factors such as being new client (AOR = 0.12; 95% CI: 0.028-0.54), injectable contraceptive users (AOR = 0.34, 95% CI: 0.15-0.80) and getting information about the contraceptive from the provider (AOR = 6.17, 95% CI: 2.47-14.4) were significantly associated with contraceptive use by client choice. Conclusions and recommendations: In this study, the magnitude of contraceptive use by client choice was lower than expected level. Therefore, regularly monitoring family planning service provision as per the national guideline is crucial to improve the contraceptive use by client choice.